Microbial Safety of Dairy Manure Fertilizer Application in Raspberry Production - Sheng, Lina; Shen, Xiaoye; Benedict, Chris; Su, Yuan; Tsai, Hsieh-Chin; Schacht, Elizabeth; Kruger, Chad E.; Drennan, Margaret; Zhu, Mei-Jun (Frontiers in Microbiology, 2019)
Dairy manure, a by-product in the dairy industry, is also a potential source of nutrients for crops. However, improper application of biological soil amendments of animal origin can be a source of contamination with enteric foodborne pathogens. A 2-year field study was conducted to evaluate impacts of dairy manure fertilizer application on the microbial safety of red raspberry (Rubus idaeus L) production. Fertilizers, including a standard synthetic fertilizer (CON), straight lagoon raw manure (SL), anaerobically digested liquid effluent (DLE), compost (COM) and dairy manure-derived refined fertilizers including ammonium sulfate (AS) and phosphorous solid (PS), were randomly applied in quadruplicate to raspberry plots. Soil, fertilizer, foliar, and raspberry fruit samples were collected during the cropping season for the quantification of indicator microorganisms (total coliform and generic Escherichia coli) and detection of important foodborne pathogens (Shiga toxin-producing E. coli (STEC), Salmonella, and Listeria monocytogenes). Counts of total coliforms in soil were stable over the 2017 cropping season and were not impacted by fertilizer application. In 2018, total coliforms increased with season and soils treated with COM had a significantly higher coliform number than those treated with CON. Both total coliform and generic E. coli in raspberry fruit samples were below the detectable level (3 most probable number/g) regardless of fertilizer types. In both years, no STEC or L. monocytogenes was detected from any of the collected samples regardless of fertilizer treatments. However, Salmonella was detected in some of the fertilizers, including PS (2017), DLE (2018) and SL (2018), which was transferred to soil samples taken directly after application of these fertilizers. Salmonella was not detected in soil samples 2- or 4-month post fertilizer application, foliar, or raspberry fruit samples regardless of fertilizer applications. In summary, one-time application of raw dairy manure or dairy manure-derived fertilizers more than 4-month prior to harvest has no major impact on food safety of red raspberry (6 ft tall) production in Lynden sandy loam under good agricultural practices.